2023
DOI: 10.1503/jpn.220147
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific transcriptional signatures in the medial prefrontal cortex underlying sexually dimorphic behavioural responses to stress in rats

Abstract: Background: Converging evidence suggests that stress alters behavioural responses in a sex-specific manner; however, the underlying molecular mechanisms of stress remain largely unknown. Methods: We adapted unpredictable maternal separation (UMS) and adult restraint stress (RS) paradigms to mimic stress in rats in early life or adulthood, respectively. The sexual dimorphism of the prefrontal cortex was noted, and we performed RNA sequencing (RNA-Seq) to identify specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Together with the current findings, it is possible that HSPA4 may be targeted by K48-polyubiquitination for degradation to a larger degree in the amygdala of adult male rats than in adult female rats due to differences in total HSPA4 levels. RPL34 was also identified and has been reported to have higher expression in the medial prefrontal cortex (mPFC) of male compared to female rats [43]. The same study also reports a sex difference in Uba52 expression, where they found higher expression in the mPFC of male compared to female rats regardless of stress, which is opposite of what we previously observed in the amygdala [18].…”
Section: Discussionmentioning
confidence: 71%
“…Together with the current findings, it is possible that HSPA4 may be targeted by K48-polyubiquitination for degradation to a larger degree in the amygdala of adult male rats than in adult female rats due to differences in total HSPA4 levels. RPL34 was also identified and has been reported to have higher expression in the medial prefrontal cortex (mPFC) of male compared to female rats [43]. The same study also reports a sex difference in Uba52 expression, where they found higher expression in the mPFC of male compared to female rats regardless of stress, which is opposite of what we previously observed in the amygdala [18].…”
Section: Discussionmentioning
confidence: 71%